An efficient secretion of the protein fused to the AgfA signal sequence in Salmonella - Ho Young Kang; Ki Hwan Moon; Se Won Kim; Jeong Dong Bahk; Sang Wan Gal; KwangKeun Cho; Chul-Wook Kim; John Hwa Lee; Sam Woong Kim (African Journal of Pig Farming, 2015)
Signal sequence (SS) of surface or secreting proteins plays an important function for protein secretion in bacterial system. The SS of various proteins may mediate different level of protein excretion yield of the proteins. In order to examine the effect of SS types in protein secretion, signal sequences of Bla (– lactamase), AgfA (thin aggregative fimbriae A), StfA (Salmonella typhimurium fimbriae A) and OmpW (outer membrane protein W) were selected for the secretion of PspA protein which was used as a test protein. The PCR-amplified DNAs corresponding to each SS were cloned into the plasmid pYA3342. A primer used in PCR was designed to insert a His6-tag at the C- terminal of SS for the convenient detection of expressed SS. The 0.8 kb EcoRI-Hin dIII pspA gene was cloned into the recombinant plasmids, resulting pMMP66, pMMP67, pMMP68 and pMMP70. The S. typhimurium strains harboring the recombinant plasmids expressed the His6-tagged PspA, demonstrating in-frame fusion of PspA to each Depending upon the type of SS, cell lysate as well as secreted PspA of each Salmonella samples was found different. Relatively, S. typhimurium containing pMMP67 (carrying AgfA SS) secreted the highest level of PspA than others, and suggested that the AgfA SS mediates efficient translocation of the PspA. Conclusively, the AgfA SS mediated secretion system in pMMP67 can be used in variety fields required for the high level of protein secretion, especially antigen delivery in recombinant attenuated Salmonella vaccines.